2015
DOI: 10.1111/joic.12174
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Properties of the Fossa Ovalis as They Relate to Transseptal Punctures: A Translational Approach

Abstract: Results may provide physicians with important knowledge about what to expect when treating a possible iatrogenic atrial septal defect or help them understand the consequences of transseptal punctures. Comparative data between swine and human atrial septal tissue properties provide critical insights between the species and offer clinicians and device designers important information relative to differences in tissue behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 31 publications
0
12
2
Order By: Relevance
“…It should be noted that extensive catheter manipulation on the left side of the heart (via a transseptal puncture) also increases the risk for formation of iatrogenic atrial septal defects. 19 Additionally, transseptal punctures account for some portion of cardiac tamponade cases, so diagnostic and ablation catheters are not the sole cause. High contact forces also increase the risk for either elicitation of steam pops and/or thrombus formation.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that extensive catheter manipulation on the left side of the heart (via a transseptal puncture) also increases the risk for formation of iatrogenic atrial septal defects. 19 Additionally, transseptal punctures account for some portion of cardiac tamponade cases, so diagnostic and ablation catheters are not the sole cause. High contact forces also increase the risk for either elicitation of steam pops and/or thrombus formation.…”
Section: Discussionmentioning
confidence: 99%
“…grouped iASD incidence from these studies and found an average iASD prevalence of >35% immediately following the procedure, 20% at 1–6 month follow-up, and >10% at 6 months [30]. A direct correlation between catheter size, iASD diameter, and prevalence[10, 16] may explain the higher iASD prevalence following MitraClip placement compared with non-MitraClip procedures.…”
Section: Prevalencementioning
confidence: 99%
“…The haemodynamic consequences in these procedures are thought to be minimal and therefore closure of the iASD is not routinely performed. As iASD size increases exponentially with catheter size[10], the iASD following the MitraClip procedure (Fig. 2) might induce haemodynamically significant shunting, although little is known on this subject.
Fig.
…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the mechanical properties, both materials presented a Young modulus higher (720 kPa for the silicone and 110 kPa for the PVA‐C) than the expected for the real tissue. Previous studies reported that the Young modulus of the entire atrial wall varies between 20 and 70 kPa, being not uniform along the entire wall . Specifically for the thin wall region, a value around of 30 kPa is expected .…”
Section: Discussionmentioning
confidence: 89%
“…Previous studies reported that the Young modulus of the entire atrial wall varies between 20 and 70 kPa, being not uniform along the entire wall . Specifically for the thin wall region, a value around of 30 kPa is expected . In this sense, the developed phantom models are stiffer than in reality and assume a homogeneous elasticity throughout the entire model, consequently presenting a sub‐optimal performance to mimic the real deformations of the atrial walls.…”
Section: Discussionmentioning
confidence: 97%